Learning to teach in the secondary school : a companion to school experience - Capel, Susan, ....-; Leask, Marilyn, ....-; Younie, Sarah, ....- (London : Routledge, 2016)
Learning to teach involves hard work and careful preparation. To become an effective teacher requires pedagogical and subject knowledge, an understanding of your pupils and how they learn, and the confidence to respond to dynamic classroom situations. Learning to Teach in the Secondary School is the market leading text for all undergraduate, postgraduate and school-based routes to qualified teacher status. It offers an in-depth and practical introduction to the knowledge, skills and understanding needed to become a confident and effective teacher. With a focus on evidence-based practice, the book includes a wealth of examples to demonstrate how to successfully apply theory to practice, and how to critically analyse your practice to maximise pupil learning. This 7th edition is fully updated in light of the latest initiatives, evidence and research in the field, offering comprehensive coverage, unit by unit, of the key concepts and skills addressed on initial teacher education courses in preparation for work in schools. The wide range of pedagogical features support both university based work - including that up to Masters Level - and school-based initial teacher education, and are designed to help you develop those qualities that lead to good practice and a successful future in education. Written by expert practitioners, thirty-six essential units include: * adopting a positive approach to managing behaviour to support learning * ways pupils learn * planning lessons, units of work and schemes of work * motivating pupils * assessment * inclusion and special educational needs * using ICT and digital technologies * pupil grouping, progression and differentiation * managing time, workload and stress * getting your first teaching post. Learning to Teach in the Secondary School provides practical help and guidance for many of the situations and potential challenges you are faced with in school.